Coffee Shop as a Value Added of Ngidam Muncar Tourism Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The Tourism Village concept is intensified by the government as one of the national development priorities in the tourism sector. This concept was developed by Muncar Village, Semarang through the “Ngidam Muncar Tourism Village”. The village government has tried to organize the area, although there are still limitations in attracting tourists. The minimal number of tourist visits indicates that Ngidam Muncar Village needs potential added value. One of the current attractions that is currently popular is the coffee shop. We can see the increasing number of coffee shops that are bustling in the community. Therefore, the coffee shop was chosen as a solution offer for the current value added of a tourist village. The purpose of this service is to provide counseling related to the management of "Coffee Shop as a Value Added in Ngidam Muncar Tourism Village Semarang". Service activities were carried out by providing an overview of Coffee Shop opportunities for the development of tourist villages as well as direct practice of setting up coffee shops and making them. The training was delivered by the expert in coffee entrepreneurs associations. By understanding the trend of coffee shop development, the value added of tourist villages is expected to be more optimal. The expected outcome target is that the participants have a theoretical and practical picture in developing a coffee shop in a tourist village area.